1996
DOI: 10.1056/nejm199610033351404
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Infection in Infants as Protection against Subsequent Infections

Abstract: In infants, natural rotavirus infection confers protection against subsequent infection. This protection increases with each new infection and reduces the severity of the diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
637
1
43

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 823 publications
(728 citation statements)
references
References 35 publications
30
637
1
43
Order By: Relevance
“…6,7 This variation has been attributed to less severe disease in young children due to persistence of maternal antibodies. 12,13 In a multicentric study conducted by Kang et al, rotavirus detection rates were greatest among children aged 6e23 months. 14 The association between seasonality and rotavirus diarrhea has not been clear with evidence both for and against it.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 This variation has been attributed to less severe disease in young children due to persistence of maternal antibodies. 12,13 In a multicentric study conducted by Kang et al, rotavirus detection rates were greatest among children aged 6e23 months. 14 The association between seasonality and rotavirus diarrhea has not been clear with evidence both for and against it.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys carried out in Mexico show that protection increases with successive reinfections and that surveyed children did not develop RV-A gastroenteritis after two RV-A infections (Velazquez et al 1996). These findings encouraged the development of RV-A vaccines.…”
mentioning
confidence: 90%
“…Typically, most severe rotaviral disease occurs upon primary infection, usually in infants less than 5 years old, although this does not induce complete protective immunity. Repeat infections are common but generally less severe in outcome [2,3] due to development of a partially effective immune response. Rotaviral disease is also common amongst the elderly, particularly through outbreaks in residential care [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many studies investigating the epidemiology of disease and repeat infection (symptomatic and asymptomatic) in children [2,3,[9][10][11][12][13] less attention has focused on infection and disease in other age groups. Studies which have investigated rotaviral infection in older age groups have long suggested that infection rates could be high, especially in case contacts [14,15].…”
Section: Introductionmentioning
confidence: 99%